Enhancing treatment adherence in dialysis patients through digital health interventions: a systematic review and meta-analysis of randomized controlled trials - Zhe Zhang; Xin-Ting Liang; Xu-Wei He; Xian Zhang; Rui Tang; Rui-Duo Fang; Jin-Zhu Li (Renal Failure)
Objective To systematically assess the efficacy of digital health interventions (DHIs) for improving treatment adherence among dialysis patients through a meta-analysis of randomized controlled trials (RCTs).Methods Five databases were systematically searched from inception to April 2024. Meta-analyses were performed to calculate standardized mean differences (SMDs) and 95% confidence intervals (CIs) for adherence outcomes. Evidence quality was evaluated using the GRADE approach.Results Seventeen RCTs involving 1,438 dialysis patients were analyzed. DHIs significantly improved overall adherence (SMD 1.88 [95% CI: 0.46–3.29]; 4 trials, low-certainty evidence). Specifically, DHIs demonstrated large improvements in medication adherence (SMD 1.45 [95% CI 0.38–2.52]; 4 trials, 300 patients; low-certainty evidence) and dialysis treatment adherence (SMD 1.88 [95% CI 0.46–3.29]; 4 trials, 245 patients; low-certainty evidence). Moderate improvements were observed in dietary adherence (SMD 0.58 [95% CI 0.25–0.91]; 4 trials, 344 patients; moderate-certainty evidence) and fluid management adherence (SMD −0.36 [95% CI −0.64 to −0.07]; 7 trials, 619 patients; moderate-certainty evidence).Conclusions Digital health interventions effectively enhance multiple dimensions of treatment adherence in dialysis patients, underscoring their value for incorporation into routine clinical practice.